Sestrin2 promotes Unc‐51‐like kinase 1 mediated phosphorylation of p62/sequestosome‐1. (28th July 2014) - Ro, Seung‐Hyun; Semple, Ian A.; Park, Haewon; Park, Haeli; Park, Hwan‐Woo; Kim, Myungjin; Kim, Jeong Sig; Lee, Jun Hee
<x xml:space="preserve">Abstract</x> Autophagy is a homeostatic process that is important for degrading protein aggregates, nutrient deposits, dysfunctional organelles and several signaling molecules. p62/sequestosome‐1 is a protein that binds to several autophagy substrates, such as ubiquitinated proteins, damaged mitochondria and signaling molecules such as an Nrf2 inhibitor Keap1, promoting their autophagic degradation. Sestrin2, a stress‐inducible protein, has recently been shown to bind to p62 and promote autophagic degradation of such p62 targets. Because Sestrin2 is a metabolic regulator that suppresses diverse age‐ and obesity‐associated pathologies, the autophagy‐controlling function of Sestrin2 may be important for its other physiological functions. However, the molecular mechanism of how Sestrin2 can promote clearance of p62‐associated proteins has been unclear. Here we show that Sestrin2 physically associates with Unc‐51‐like protein kinase 1 (ULK1) and p62 to form a complex in which both Sestrin2 and p62 become phosphorylated by ULK1 at multiple sites. Ser403 of p62, whose phosphorylation is known to promote autophagic degradation of p62 and its targets, is among the sites phosphorylated by ULK1. ULK1‐mediated p62 phosphorylation was facilitated by Sestrin2 in cells as well as in in vitro kinase assays. Consistent with this finding, oligomycin‐induced energy deprivation, which strongly activates ULK1, provoked a robust Ser403 phosphorylation of p62 in wild‐type mouse embryonic fibroblasts. However, in ULK1/2‐ and Sestrin2‐deficient mouse embryonic fibroblasts, oligomycin‐induced p62 phosphorylation was dramatically attenuated, suggesting that endogenous Sestrin2‐ULK1/2 mainly mediates p62 phosphorylation in response to energetic stress. Taken together, this study identifies ULK1 as a new p62 Ser403 kinase and establishes Sestrin2 as a promoter of ULK1‐mediated p62 phosphorylation. Structured digital abstract ULK1 physically interacts with Sestrin2 by pull down (View interaction) p62 physically interacts with Sestrin2 by anti tag coimmunoprecipitation (1, 2) p62 physically interacts with ULK1 by anti tag coimmunoprecipitation (View interaction) Sestrin2 physically interacts with p62 and ULK1 by anti bait coip (View interaction) Sestrin2 physically interacts with ULK1, FIP200 and Atg13 by anti tag coimmunoprecipitation (View interaction) p62 physically interacts with ULK1 and Sestrin2 by anti tag coimmunoprecipitation (View interaction) ULK1 physically interacts with Sestrin2 by anti tag coimmunoprecipitation (1, 2, 3) p62 physically interacts with Sestrin2 by pull down (View interaction) p62 physically interacts with Sestrin2 by anti tag coimmunoprecipitation (View interaction)